Markers to Predict the Efficacy of Bevacizumab in the Treatment of Metastatic Colorectal Cancer. Issue 4 (July 2014) - Varol, Umut; Yildiz, Ibrahim; Salman, Tarik; Karabulut, Bulent; Uslu, Ruchan
The identification of clinical, biochemical and molecular markers to predict or monitor the efficacy of bevacizumab represents a major point in the treatment of patients with metastatic colorectal cancer. Studies and genetic analyses have been conducted to identify a predictive biomarker of bevacizumab efficacy. However, genes of the angiogenic pathway and angiogenic biomarkers vary substantially, thereby causing interindividual differences that complicate the identification of predictors for anti-vascular endothelial growth factor drugs like bevacizumab. So, the current challenge in bevacizumab treatment is to find predictive markers and implement them in clinical practice. In this review we have summarized the potential candidate biomarkers that may have a role in identifying patients who benefit most from bevacizumab treatment.